The Most Valuable Global Brands and Condition of Economies: a Spatial Approach - Wioleta Kucharska; Karol Flisikowski (Institute of Economic Research (IER), 2017)
Research background: Brands are considered to be the most valuable asset of a company. Some of them achieve spectacular global results. The significance of global brands is proved by the fact that their value is often greater than the sum of all company's net assets. Purpose of the article: The aim of this article is to highlight that brand value does not only create company's value but also leverages economies. We claim that even though global brands are sold worldwide they more strongly contribute to the development of economies in the countries where these brands' owners are located. Methodology/methods: Based on 500 Brandirectory, the most Valuable Global Brands ranking powered by Brand Finance, we have discovered a spatial-economic autocorrelation to illustrate the potential interdependency between GDP and brand value which constitutes a foundation for further construction of a spatial regression model. Because the ranking data was only available for the year 2014, the analyses were performed for 33 selected countries. Findings: Our findings confirm the hypothesis that assumptive spatial dependencies matter for the investigated relationship between brand value and GDP. The evidence is based on the spatial error and the spatial lag model, although the former has a slightly better performance than the latter alternative.
Keywords: F63; M31; 330; GDP; brand value; spatial economics